2007
DOI: 10.4049/jimmunol.179.12.8509
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Homing Receptors on Effector Leukocytes Are Differentially Sensitive to Glyco-Metabolic Antagonism in Allergic Contact Dermatitis

Abstract: T cell recruitment into inflamed skin is dependent on skin-homing receptor binding to endothelial (E)- and platelet (P)-selectin. These T cell receptors, or E- and P-selectin ligands, can be targeted by the metabolic fluorosugar inhibitor, 4-F-GlcNAc, to blunt cutaneous inflammation. Compelling new data indicate that, in addition to T cells, NK cells are also recruited to inflamed skin in allergic contact hypersensitivity (CHS) contingent on E- and P-selectin-binding. Using a model of allergic CHS, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…4-F-GlcNAc has been shown to inhibit N-acetyllactosamine and Gal-1-binding determinant formation on membrane proteins expressed by T cells (Barthel et al, 2011) and on ovarian and colon cancer cells (Descheny et al, 2006; Dimitroff et al, 2003a; Dimitroff et al, 2003b; Gainers et al, 2007; Woynarowska et al, 1996; Woynarowska et al, 1994). Stability analysis of 4-F-GlcNAc in mouse plasma showed that the parent compound, fully acetylated 4-F-GlcNAc, exhibited a half life of ~2.3h, sufficient for uptake by relevant immune cells (Figure S1d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4-F-GlcNAc has been shown to inhibit N-acetyllactosamine and Gal-1-binding determinant formation on membrane proteins expressed by T cells (Barthel et al, 2011) and on ovarian and colon cancer cells (Descheny et al, 2006; Dimitroff et al, 2003a; Dimitroff et al, 2003b; Gainers et al, 2007; Woynarowska et al, 1996; Woynarowska et al, 1994). Stability analysis of 4-F-GlcNAc in mouse plasma showed that the parent compound, fully acetylated 4-F-GlcNAc, exhibited a half life of ~2.3h, sufficient for uptake by relevant immune cells (Figure S1d).…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the dependence of Gal-1-binding N-acetyllactosamines in Gal-1-mediated tumor immune evasion, we used a fluoro-glucosamine inhibitor of N-acetyllactosamine formation, 4-F-GlcNAc. This inhibitor prevents N-acetyllactosamine synthesis on N- and O-glycans in glyco-metabolically active immune cells and prevents consequent lectin-binding activity with relatively high specificity for Gal-1-binding determinants (Barthel et al, 2011; Descheny et al, 2006; Dimitroff et al, 2003a; Dimitroff et al, 2003b; Gainers et al, 2007; Woynarowska et al, 1996; Woynarowska et al, 1994). Importantly, in this report, we show that diminution of Gal-1 binding on activated T cells via 4-F-GlcNAc treatment can alleviate Gal-1-mediated T cell apoptotic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PC-3 empty or FT cells stably expressing EGFP were injected into the left ventricle of Rag2/Janus kinase(Jak)-3 double null mice deficient in T, B, and NK cells (Fig. S4) (26,27), and analyzed over a 24 h period for PCa cell retention in BM, lungs. and spleen.…”
Section: Ft3 Ft6 and Ft7 Induce E-selectin-mediated Adhesion Of Metmentioning
confidence: 99%
“…This molecule reduces selectin-mediated cutaneous lymphocyte-associated antigen (CLA ϩ ) T-cell adhesion in vitro, 28 and in in vivo models of skin inflammation. [29][30][31] Because O-linked glycans linked to PSGL-1 and other glycoproteins participate as important selectin ligands and because the attachment of GalNAc to serine/threonine residues on the peptide backbone is critical for the initiation of O-glycan assembly, we tested the hypothesis that modified monosaccharides based on GalNAc may be used to disrupt/alter the pattern of O-linked glycosylation. This can result in reduced selectin binding function.…”
Section: Introductionmentioning
confidence: 99%